DEVELOPMENT OF ONLINE RETAILING LOGISTICS FLOWS IN A GLOBALIZED DIGITAL ECONOMY - Lukiyanchuk, Irina; Panasenko, Svetlana; Kazantseva, Svetlana; Lebedev, Kostyantyn; Lebedeva, Olga (Revista Inclusiones, 2020)
The article deals with the development of logistics flows of online retailing in the context of the digital economy globalization. It is revealed that interaction in the global space requires not only technological adaptation but also a radical restructuring of business processes at the enterprise within the information model of resource flows, as well as distinguishing areas where informatization will give the greatest efficiency. It is proved that the transition from using individual web resources to integrating them into business processes has led to the need for cloud computing services. It is revealed that these services are used by enterprises for many reasons, including the need to establish an appropriate level of information security, providing business with information mobility, and reducing the cost of maintaining information infrastructure. It is determined that cloud services are key ones for building an effective online retailing logistics system from the standpoint of financial flow management.